Mixed rectilinear sources localization under unknown mutual coupling. Issue 4 (March 2019) - Chen, Hua; Liu, Wei; Zhu, Wei-Ping; Swamy, M.N.S.; Wang, Qing
Abstract: In this paper, a novel rectilinearity-based localization method for mixed near-field (NF) and far-field (FF) sources is proposed under unknown mutual coupling. The multiple parameters including direction of arrival (DOA), range and mutual coupling coefficient (MCC) are decoupled, thus only three one-dimensional (1-D) spectral searches are required to estimate the parameters of mixed rectilinear signals successively. Furthermore, the closed-form deterministic Cramer–Rao bound (CRB) of the concerned problem is also derived. Simulation results are provided to demonstrate the effectiveness of the proposed method for the classification and localization of mixed rectilinear sources.